The Rise and Fall of the Third Chimpanzee: How Our Animal Heritage Affects the Way We Live - Hamed Vahdati Nasab (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book of Rise and Fall of the Third Chimpanzee: How Our Animal Heritage Affects the Way We Live, written by Jared Diamond is one of the best works in linking the evolutionary biology and cultural complexity of human societies. The author attempted to search for many of the social behaviors of modern humans in inherited biology from ancient ancestors of humans and has been very successful in this regard. Perhaps the only disadvantage of the book is the lack of updating its content, a subject that has been criticized. In this article, the author attempts to express the contents of a book and, in some cases, update it in cases where more recent discoveries than the time of writing the book have been confirmed by some writers. This book is divided into five sections. The first and second sections (the first seven chapters) deal with evidence about bones, tools, and genes, which are utilized for archeological and biological documentation. The third section (chapters 8-12) pertains to the cultural characteristics which distinguish humans from animals. In the last two sections of the book, the author succinctly reviews the devastating features of humankind and trace the origins of some of these features in the ancient biology.